PENGARUH ATRAKSI WISATA, FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG DI TAMAN MARGASATWA RAGUNAN JAKARTA - Stevianus Stevianus (Universitas Gunadarma, 2015)
This research is motivated by the growth rate of the high tourist in Jakarta that is not matched by an increase in the number of tourists are balanced. The problem in this research is